INCREASING SKILLS READING FICTIONS OR NON-FICTION BOOKS AND STUDY LEARNING STUDENTS THROUGH TRANSACTIONAL READING STRATEGY APPROACH - Ana Syahbaniarwati; Teti Sobari (IKIP Siliwangi, 2018)
This based on the problems that occur in the field in reading ability and student's independence to learn Indonesian is still low. As teachers have a great responsibility to the students so that it must be able to prepare the planning of learning is steady then as a teacher must be able to adjust the learning materials with the environment where the students live and can apply in everyday life. The research method used in this research is quasi-experiment with nonequivalent control group design type, that is experiment group or control group is not chosen randomly. The population in this study is all with two class samples totaling 60 students. Based on the research, the average value of the final test of the experimental class is 73,67 while in the control class get the average of the final test value is 60,23. Based on the calculation of the initial test of T-test obtained 0, 002 while the calculation of Mann-Whitney U obtained 0.000 results. The results of this study indicate that student learning outcomes by using the approach of transactional reading strategy is better than the lecture method on the subjects of reading fiction books.